The Impact of Venture Capital on Economic Growth - Steven Poelhekke; Benjamin Wache (Tinbergen Institute, 2023)
Does venture capital (VC) investment yield economic growth? A large literature studies the effect of VC investments on firm-level activity, but its effects on economic growth are less well understood. We identify the effect of VC investment flows on destination county employment, wages, and establishment creation, using a novel instrument that captures the 'social connectedness' of counties to major sources of VC investment. Using detailed data on VC flows from investors to companies, we find a large positive impact of VC investment, suggesting that strong social connections to large venture capital hubs are an important contributor to regional economic growth.
Keywords: R11; G24; G41; 330; Growth; venture capital; social connectedness